Strategi Diversifikasi Produk Buku Fiksi Sebagai Pengembangan Karya Tugas Akhir Penerbitan - Refi Yuliana; Suratni; Prily Fitria Aziz (MUKASI: Jurnal Ilmu Komunikasi, 2022)
This research departs from the lack of development in the work of the Final Project students of the Publishing Study Program, especially in books with the fiction genre. This limitation causes the work produced in terms of content and medium is still monotonous and has not developed in the desired direction. This research uses the concept of product development strategy which is commonly used in business and industry, especially the publishing industry. This study uses a qualitative descriptive method to analyze, describe, and explain the diversification that may be used for students of Publishing. The object of the research is the student's final thesis product Publishing from 2015 to 2020. This research also aims to find a new formulation for writing a publishing final project product, especially in the fiction category. The results of this study show that in the 2015 to 2020 period, there are only 4 types of fiction that keep repeating itself, and there is only 1 work in the form of a flashlight book as part of manual product development. This research resulted in a further mapping of the stages of diversification that students could choose and their product forms.